Cyberbullying behavior: A study of emotional maturity Yogyakarta students - Chornelius Hutagaol (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2021)
Purpose - The research objective was to determine the relationship between emotional maturity and cyberbullying behavior among students.Method - This research is a case study using a quantitative method based on a post-positivism approach. The sampling technique in this study using purposive sampling technique. The number of subjects in this study amounted to 60 students. The data analysis technique used product moment correlation.Result - The results of the research analysis using the